6 Resistin mediates sex-dependent effects of perivascular adipose tissue on vascular function in the shrsp. (1st April 1997) - McNeilly, Sarah; Small, Heather Y; Mary, Sheon; Sheikh, Adam; Delles, Christian
Abstract : Introduction: Premenopausal women are relatively protected against hypertension compared to males. Oestrogen levels have been identified as a potential underlying cause, but many of the pathophysiological mechanisms remain to be determined. Altered perivascular adipose tissue (PVAT) function has been identified to have vasoactive effects. However, in hypertension, sex-dependent differences of PVAT have not yet been explored. Hypothesis: Sex-dependent effects of PVAT mediate altered vascular function in hypertension. Approach and result: The effect of PVAT was investigated on resistance vessels of 16 week old male and female stroke-prone spontaneously hypertensive rats (SHRSP). This preclinical model of hypertension presents with a sex-difference in the development of hypertension comparable to humans. Wire-myography was used on 3rd order mesenteric vessels to assess vascular function. Noradrenaline mediated vasoconstriction was increased in SHRSP males compared to females (maximum contraction: male +PVAT 113.3±1.1% vs female +PVAT 91.4%±11.36%). KATP channel-mediated vasorelaxation by cromakalim was impaired in males compared to females (maximum relaxation: male +PVAT 46.9±3.9% vs female +PVAT 97.3%±2.7%). A cross-over study assessing function of male PVAT on female vessels and vice versa confirmed the reduced KATP mediated vasorelaxation induced by male PVAT (maximum relaxation: female +PVATfemale 90.6±1.4% vs female +PVATmale 65.8%±3.5%). To explore the cause of sex-dependent differences in PVAT an adipokine array with subsequent western blot validation was carried out. This identified resistin as a potential modifier of vascular reactivity. Resistin was increased by approximately 2-fold in SHRSP male mesenteric PVAT. Further wire-myography experiments with male and female vessels pre-treated with resistin (40 ng/ml) showed no difference in response to noradrenaline. However, vasorelaxation in response to cromakalim was significantly impaired in resistin treated female vessels, similar to levels observed in male vessels (maximum relaxation: female +PVAT 97.3±0.9% vs female +PVAT +resistin[40 ng/ml] 36.8%±2.3%). Conclusion: These findings indicate a novel role for resistin in sex-dependent PVAT mediated vascular function in hypertension through a KATP channel mediated mechanism.